2015
DOI: 10.1007/s00441-015-2198-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of FABP genes in protochordates, Ciona intestinalis and Branchiostoma belcheri

Abstract: Fatty-acid-binding proteins (FABPs) are small intracellular proteins associated with the transportation of fatty acids. Members of the FABPs share similar amino acid sequences and tertiary structures and form, together with a member of the cellular retinol-binding proteins (CRBPs), the intracellular-lipid-binding protein (iLBP) family. In vertebrates, several types of FABP have been isolated and classified into three subfamilies: 2-4. In invertebrates, several FABP-related proteins have been reported in protos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It is known that in mice, the pancreas derives from the foregut endoderm, which is formed by a small field of epithelial precursor cells expressed by pancreatic duodenal transcription factor 1 [ 18 ]. A hepatopancreas (also called a pyloric gland), as an accessory organ, is a branching structure developed from the boundary between the stomach and intestine in ascidians [ 48 , 49 ]. In a previous study, the expression of Ciona homologs of pancreatic- and gastric-related exocrine enzyme genes and their transcriptional regulator genes is restricted to the Ciona stomach [ 15 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in mice, the pancreas derives from the foregut endoderm, which is formed by a small field of epithelial precursor cells expressed by pancreatic duodenal transcription factor 1 [ 18 ]. A hepatopancreas (also called a pyloric gland), as an accessory organ, is a branching structure developed from the boundary between the stomach and intestine in ascidians [ 48 , 49 ]. In a previous study, the expression of Ciona homologs of pancreatic- and gastric-related exocrine enzyme genes and their transcriptional regulator genes is restricted to the Ciona stomach [ 15 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that several fabp-like genes have RA transportation capacity in protostomes, although their orthology with vertebrate CRABP genes is not supported [29,30]. In deuterostomes, Orito et al [31] classified vertebrate FABPs into three subfamilies and identified the basal gene(s) of each subfamily using urochordate genomic data; however, they did not identify any genes that were orthologous with the crabp and rbp genes, suggesting that CRABPs are components specific to vertebrates [31]. By contrast, based on sea urchin genomic data, one crabp gene, two rbp genes (rbp-1 and rbp-2), and two fabp genes (fabp-1 and fabp-2) were identified [32], although no phylogenetic analysis has been conducted.…”
Section: Ra Transportmentioning
confidence: 97%